WHO Is Recommending against the Use of COVID-19 Convalescent Plasma in Immunocompromised Patients? - Massimo Franchini; Arturo Casadevall; Michael J. Joyner; Daniele Focosi (Life, 2023)
Since December 2019, SARS-CoV-2 is ravaging the globe, currently accounting for over 660 million infected people and more than 6 [...]